Low Contrast Visual Acuity Might Help to Detect Previous Optic Neuritis - Park, Soo-Hyun; Park, Choul Yong; Shin, Young Joo; Jeong, Kyoung Sook; Kim, Nam-Hee (Frontiers in Neurology, 2020)
Optic neuritis (ON) has been considered to be an important factor in the diagnosis of multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD), making ON detection increasingly critical for early diagnosis. Furthermore, subclinical ONs presenting no distinct decrease in visual acuity can be missed. Low contrast visual acuity (LC-VA) is known to be able to capture visual loss not seen in conventional high-contrast visual acuity (HC-VA) in MS. Therefore, to increase the sensitivity of ON detection, we investigated the advantage of LC-VA over conventional HC-VA. One hundred and eight patients with demyelinating disease (35 MS, 73 NMOSD) with ON at least 3 months prior and 35 controls underwent neuro-ophthalmic evaluation, including best-corrected conventional high contrast visual acuity (HC-VA) and 2.5% and 1.25% low contrast visual acuity (LC-VA). Receiver operating characteristic (ROC) curve analysis and the area under the curve (AUC) of various visual functions were used to determine the most relevant visual function test for the detection of optic nerve involvement. Additionally, the optimal cutoff point was obtained from the Youden index (J-index) as the points with the best sensitivity-specificity balance. When distinguishing ON from non-ON, the area under the ROC curve (AUC) was highest for the 2.5% LC-VA (0.835, P < 0.001; sensitivity 71.5%, specificity 88.6%), while it was 0.710 (P < 0.001) for the HC-VA and 0.770 (P < 0.001) for the 1.25% LC-VA. In discriminating between controls and ON, the AUC was also highest for the 2.5% LC-VA 0.754 (P < 0.001; sensitivity 71.5%, specificity 78.5%), while it was 0.719 (P < 0.001) for HC-VA and 0.688 (P < 0.001) for 1.25% LC-VA. In eyes with a history of ON (n = 137), the HC-VA and 2.5% LC-VA were abnormal in 64.2 and 71.5%, respectively (P < 0.001), with their combination detecting abnormalities in approximately 85.4% (P < 0.001). The 2.5% LC-VA was superior to HC-VA in detecting ON when distinguishing ON from non-ON or control. The 2.5% LC-VA might be a useful, feasible, and rapid method to detect ON. Furthermore, combining 2.5% LC-VA with conventional HC-VA would be better for detecting optic nerve involvements.